Inequalities, geography and emissions - (:unkn) unknown (My University, 2025)
The relationship between environmental policy and economic inequalities between countries is relatively well established. In particular, environmental amenities being a normal good, rich countries tend to adopt greener policies than poorer ones. In contrast, the link between the environment and inequalities within countries is a lot less well understood and much less analyzed. This is not because of a lack of importance: regional disparities within countries are large, sometimes even larger than across countries. Neither is this due to a lack of relevance: richer regions or income groups may care more for the environment within a given nation, which in turn will shape the national policy stance. Rather, the lack of evidence is essentially due to a lack of data: those at the national level are easily available, but those at the subnational level are still scarce and often non-comparable across countries. The main objective of this research project is to study the role of within-country inequalities on environmental policy choices. Relying on recent data sources that contain economic, geographic and environmental variables at the regional level allows for a systematic analysis of regional disparities within countries, and of their various links with the environment. How do within-country disparities in per capita emissions compare with between-country ones? Have they been converging recently? Is there a significant link between regional income inequalities and national emissions, and how does this position the pursuit of social equity and environmental protection at the world-wide level: in the same wagon or on a collision course? The project has two parts. First, by merging three different data sources, we construct a new database that reports anthropogenic emissions, GDP, population and geographic characteristics for thousands of grid cells on the Earth’s surface over the 1990-2005 period. This will allow us to analyze the world distribution of several types of emissions (including not only direct Greenhouse Gases but also ozone precursor gases and other substances), and to propose several inequality measures. Second, using econometric techniques, and controlling for geographic factors, we propose to estimate by how much economic inequalities affect emissions and environmental policy. To do this, we will regress emissions per capita at the cell level on income per capita and other controls. We will also investigate whether emissions or environmental policy proxies at the national level are affected by within-country economic and environmental inequality. All regressions will be performed using state of the art econometric techniques, and testing for the presence of neighbouring (or spatial) effects. The project enriches our knowledge in several respects. The unique data collection and associated framework will allow us to provide a novel descriptive analysis that is both global in scope and detailed in terms of regional disaggregation. The project proposes new ways of calculating inequalities that are more appropriate to the analysis of emissions. In terms of observation units, countries are replaced by grid cells, which are more comparable to one another, and more suitable to uncover geographic disparities or regional agglomeration effects. Associated regression estimates will allow for a better understanding of the determinants of anthropogenic emissions and for a simulation of the impact of environmental and distributional policies (taking these as exogenous) on emissions. In addition, regressions results will also allow us to estimate if economic inequalities and geographic characteristics are important determinants of environmental policies (considering them endogenous in a political-economy setting).
Keywords: inequalities; environmental regulation; emissions; geographic distribution